The experiences of speech pathology referral and communicative participation in adults with cerebellar ataxia. - Hilger, Allison; Dunne-Platero, Kylie (International Journal of Speech-Language Pathology, 2023)
The purpose of this study was to identify potential barriers to speech pathology referral in ataxia, as well as potential factors influencing satisfaction with speech pathology and communicative participation. An online survey study included questions about participant demographics, referral and access to speech pathology, satisfaction with speech pathology, and communicative participation via the Communicative Participation Item Bank (CPIB). We analysed 118 eligible responses from individuals with ataxia. Results from Bayesian regression models indicated that the overall referral rate to speech pathology was 64% for the respondents with a speech impairment, predicted by lower income, less education, and greater self-perceived speech severity. Additionally, sex, self-perceived speech severity, and length of speech impairment predicted more restricted communicative participation. For the respondents who were referred for speech pathology, overall satisfaction with speech pathology was neutral to high but most individuals reported little to no improvement in their speech. Referral rate to speech pathology was low given that dysarthria and dysphagia are highly likely to occur in ataxia. Considerations should be made for perceived speech severity, sex, and length of speech impairment in evaluating communicative participation. Lastly, there is a vital need for evidence-based treatment for ataxic dysarthria.